Strategy for the bioconversion of palm oil mill effluent into volatile fatty acids for the production of biodegradable polyhdroxyalkanoates / Lee Wee Shen - Lee, Wee Shen (2014)
The focus of wastewater management has evolved from treatment technology into resource recovery, which permits simultaneous waste minimization and value-added product generation. This study aims to develop a strategy for the biotransformation of the highly polluting palm oil mill effluent (POME) into volatile fatty acids (VFA) for the generation of biodegradable plastics – polyhydroxyalkanoates (PHA). The influence of solids retention time (SRT; infinite SRT, 9 d and 6 d) and temperature (30°C, 40°C and 55°C) on the production of VFA by acidogenic fermentation of POME was first investigated. Performing acidogenic fermentation at infinite SRT resulted in gradual loss of acidogenic activity with a drop in the degree of acidification (DA) from 50% to 6% progressively. Using 6-d SRT led to higher DA of 48% as compared to 33% achieved at 9-d SRT. On the other hand, the production of VFA at 30°C and 40°C outperformed that at 55°C considerably, with a DA of 48% at both 30°C and 40°C but only 7% at 55°C. The VFA-rich fermented POME was then utilized as the sole carbon substrate for PHA production by activated sludge. Prior to PHA production, activated sludge was subjected to aerobic dynamic feeding (ADF) process to enhance its PHA storage capacity through cultivation and enrichment of PHA-accumulating organisms. In the ADF process, fermented POME was employed as the sole carbon substrate and supplementary nutrient solution was provided to assist microbial growth. After 74 days of cultivation, the PHA storage capacity of the sludge improved significantly. The cultivated sludge could accumulate 64 wt% PHA per sludge dry weight at the end of the batch PHA production experiment. This was significantly higher than that achieved by the seed sludge at 4 wt%. . The effect of pH and air supply rate on the production of PHA by activated sludge was subsequently examined. It was found that neutral condition could lead to higher PHA content of 64 wt% PHA per sludge dry weight in comparison with acidic (0.5 wt% at pH 4.5) and alkaline (48 wt% and 32 wt% at pH 8 and pH 9 respectively) conditions. On the other hand, the performance of PHA production improved with the increase in the supply of air to the reactor in a range of 0.2-1.0 vvm. The PHA content attained at 1.0 vvm was 45 wt%, which was approximately 2 times and 3 times higher than that achieved at 0.5 vvm and 0.2 vvm respectively. The above results have demonstrated the feasibility of converting POME into PHA through a three-stage operating strategy which consists of acidogenic fermentation of POME, cultivation of PHA-accumulating organisms and production of PHA. This bioconversion scheme offers the palm oil industry a more meaningful alternative to manage POME. Unlike the current industrial practice that focuses on treating the pollutants in POME to meet the environmental regulations, the proposed scheme considers the pollutants as valuable feedstock and transforms them into VFA and subsequently into environmental-friendly PHA. Such transformation helps to foster the transition to a more sustainable palm oil industry.